2011
DOI: 10.1002/jmri.22496
|View full text |Cite
|
Sign up to set email alerts
|

Fast T2*‐weighted MRI of the prostate at 3 tesla

Abstract: Purpose To describe a rapid T2*-weighted (T2*W), three-dimensional (3D) echo planar imaging (EPI) sequence and its application in mapping local magnetic susceptibility variations in 3 Tesla (T) prostate MRI. To compare the sensitivity of T2*W EPI with routinely used T1-weighted turbo-spin echo sequence (T1W TSE) in detecting hemorrhage and the implications on sequences sensitive to field inhomogeneities such as MR spectroscopy (MRS). Materials and Methods B0 susceptibility weighted mapping was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…T2* relaxation time is becoming a novel quantitative biomarker to predict tumor cell density, and pulse sequence optimizations suited for prostate MRI have received increased attention. Hardman et al (11) established a rapid T2*W, three-dimensional (3D) EPI sequence and its application in the mapping of local magnetic susceptibility variations in 3.0T prostate MRI. However, these researchers only compared the sensitivity of T2* with routinely used T1W TSE in the detection of hemorrhage and the implications on sequences that are sensitive to field inhomogeneities, such as MR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2* relaxation time is becoming a novel quantitative biomarker to predict tumor cell density, and pulse sequence optimizations suited for prostate MRI have received increased attention. Hardman et al (11) established a rapid T2*W, three-dimensional (3D) EPI sequence and its application in the mapping of local magnetic susceptibility variations in 3.0T prostate MRI. However, these researchers only compared the sensitivity of T2* with routinely used T1W TSE in the detection of hemorrhage and the implications on sequences that are sensitive to field inhomogeneities, such as MR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…New treatment strategies, especially PCa focal therapy, have emerged recently, such as external radiation therapy, image-guided brachytherapy, cryotherapy, and highintensity focused ultrasound (US), which require more accurate diagnostics beyond tumor staging, and it is essential to provide more precise information on PCa detection and localization (4)(5)(6)(7)(8). T2*-weighted (T2*W) imaging was used recently in different body regions (myocardium, articular cartilage) (9)(10)(11). Korteweg et al (12) reported significant difference in the mean T2* value constants between malignant and benign nodes.…”
Section: Introductionmentioning
confidence: 99%
“…In different body regions, T 2 * weighted imaging is applied to many organs. 15,16 In addition, sensitivity differences between nonhaemorrhagic and haemorrhagic regions can be recognized by T 2 * weighted imaging, as reported by Hardman et al 17 Moreover, increasing attention has been focused on pulse sequence optimization suitable for prostate MRI. Hardman et al used a rapid three-dimensional T 2 * weighted echoplanar imaging (EPI) sequence to map the local magnetic sensitivity differences on 3.0-T prostate MRIs.…”
Section: Introductionmentioning
confidence: 91%